Sosialisasi Pemilihan Prioritas Penerima Bantuan Dana Sosial Menggunakan Algoritma Clustering di Kelurahan Tengah Kecamatan Pelayangan - Yurinanda, Sherli; Sarmada, Sarmada; Sormin, Corry; Rozi, Syamsyida; Multhadah, Cut (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
Poverty is one of the problems that must be eradicated. The government's policies for poverty alleviation is the provision of social assistance funds. But the government must consider the eligibility of the recipients of the social assistance. Since 2021-2023, the poverty rate in Jambi Province has been recorded at over 250 thousand people each year. Of the several districts/cities in Jambi Province, Jambi City contributes the largest number of poor people. Tengah Village is one of the villages in Pelayangan District, Jambi City. As an effort to support the provision of targeted social assistance, a clustering algorithm is used group objects based on certain characteristics. One of the analysis in the clustering is the K-Means algorithm. This community service activity is the socialization of the use of clustering algorithms to help group data on social assistance recipients. The activity was attended by staff and RT heads in Tengah Village. Based on the evaluation, as many as 72,7% of the participants who attended stated that they were very satisfied, in addition they stated that this activity was very useful in supporting the decision to select priority recipients of social fund assistance in the Tengah Village.